Titus Andronicus - Shakespeare, William, 1564-1616; Cajander, Paavo Emil, 1846-1913 (Salt Lake City, UT : Project Gutenberg, 2007)
"Titus Andronicus" by William Shakespeare is a tragedy written between 1588 and 1593. After returning victorious from war, Roman general Titus presents the captured Queen of the Goths, Tamora, to the new emperor$1 (Bwho takes her as his wife. When Titus sacrifices her eldest son, Tamora vows revenge from her new position of power. What follows is a brutal cycle of violence, mutilation, and retribution that engulfs both families, spiraling toward a bloody conclusion at a fateful feast. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/Titus_Andronicus
Release date is 2007-04-16
Produced by Tapio Riikonen
Keywords: Tragedies (Drama); Andronicus, Titus (Legendary character) -- Drama; Goths -- Drama; Generals -- Drama; Rome -- History -- Germanic invasions, 3rd-6th centuries -- Drama; Historical drama